2007
DOI: 10.1186/1742-4690-4-71
|View full text |Cite
|
Sign up to set email alerts
|

Detection, characterization and regulation of antisense transcripts in HIV-1

Abstract: These results demonstrate for the first time that antisense transcription exists in HIV-1 in the context of infection. Possible translation of the predicted antisense ORF in this transcript should thus be re-examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
134
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(138 citation statements)
references
References 42 publications
4
134
0
Order By: Relevance
“…Importantly, these CTL responses are not limited to ARFs in the sense direction, but may also target antisense-encoded ARFs (5,6). Antisense transcription of known host genes in human and rodent cells has been extensively described (7)(8)(9)(10), and the existence of an antisense protein (ASP) in HIV was first proposed more than 20 years ago (10)(11)(12). The extent to which such viral antisense transcripts encode functional proteins remains largely unknown.…”
Section: Irus-specific Cd8mentioning
confidence: 99%
“…Importantly, these CTL responses are not limited to ARFs in the sense direction, but may also target antisense-encoded ARFs (5,6). Antisense transcription of known host genes in human and rodent cells has been extensively described (7)(8)(9)(10), and the existence of an antisense protein (ASP) in HIV was first proposed more than 20 years ago (10)(11)(12). The extent to which such viral antisense transcripts encode functional proteins remains largely unknown.…”
Section: Irus-specific Cd8mentioning
confidence: 99%
“…HIV-1 | asp and env genes | overlapping genes | phylogenetic analyses | selection pressure I t is well established that retroviruses are able to perform antisense transcription from the 3′ long terminal repeat (LTR) of their proviral genome (1,2). In 1988, the existence of an ORF on the antisense strand of the HIV type 1 (HIV-1) genome was suggested (3).…”
mentioning
confidence: 99%
“…The existence of this ORF and of the encoded protein was controversial for many years, but now several pieces of evidence argue in favor of its expression (see ref. 4 for an extensive review): (i) several polyadenylated antisense transcripts capable of encoding ASP have been characterized within HIV-1-infected cells (1,5,6); (ii) it was demonstrated that the full-length ASP protein can be expressed ex vivo from the HIV-1 3′ LTR (7); (iii) ASP has been detected in freshly infected cells (2,8,9); and (iv) two recent independent clinical studies have shown the in vivo expression of ASP by detecting a cell-mediated immune response against several ASP epitopes within 30% of individuals infected with subtype B viruses (10,11) [a percentage similar to those observed with other HIV-1 proteins, e.g., Tat and Pol (12)]. Moreover, experimental results suggested that ASP could form stable aggregates, be located partially at the plasma membrane, and be associated with autophagy (4,7,8).…”
mentioning
confidence: 99%
“…If the provirus integrates in introns of host genes, the HIV antisense transcripts are spliced out and rapidly degraded. Nevertheless, HIV antisense transcripts have been detected (39,40), and they could provide an estimate of transcriptional interference in latently infected cells.…”
Section: Historical Perspectivementioning
confidence: 99%